Transaction costs in the transportation sector and infrastructure in North America : exploring harmonization of standards - Villa, Juan Carlos (CEPAL MexicoMX, 2007)
Analyzes North American truck, rail and maritime trade and transportation characteristics and operations that serve as the foundation to identify and quantify transaction costs caused by the lack of harmonized transportation regulations and infrastructure disparities. Describes opportunities to reduce or eliminate costs along with a strategy to implement actions to reduce transaction costs in the transportation sector.